2015
DOI: 10.1039/c5gc00403a
|View full text |Cite
|
Sign up to set email alerts
|

Iodine catalyzed cross-dehydrogenative C–S coupling by C(sp2)–H bond activation: direct access to aryl sulfides from aryl thiols

Abstract: A novel, efficient and unprecedented green protocol for the formation of C-S bond has been developed under metal-free conditions. This protocol involves the synthesis of aryl sulfides through the cross-dehydrogenative coupling of readily available aryl thiols with electron-rich species under 10 solvent-free conditions and the corresponding aryl sulfides are obtained in high to quantitative yields. A catalytic amount of inexpensive and non-toxic iodine drives the reaction and no exclusion of air and expensive l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(49 citation statements)
references
References 75 publications
1
47
0
1
Order By: Relevance
“…Compound 37 : Colorless oil, 75 %. 1 H NMR (300 MHz, CDCl 3 , ppm) δ =2.29 (s, 3 H), 2.98 (s, 6 H), 6.66–6.74 (m, 2 H), 7.00–7.09 (m, 4 H), 7.34–7.40 (m, 2 H) …”
Section: Methodsmentioning
confidence: 99%
“…Compound 37 : Colorless oil, 75 %. 1 H NMR (300 MHz, CDCl 3 , ppm) δ =2.29 (s, 3 H), 2.98 (s, 6 H), 6.66–6.74 (m, 2 H), 7.00–7.09 (m, 4 H), 7.34–7.40 (m, 2 H) …”
Section: Methodsmentioning
confidence: 99%
“…These sulfanylated coumarin and quinolinone derivatives have a wide range of biological and pharmacological activities, such as antifungal, antibacterial, antimicrobial, and anti‐HCV activities . Because of their importance and usefulness, several synthetic approaches for the sulfanylation of 4‐hydroxycoumarins and 4‐hydroxyquinolinones have been developed by C–S bond formation between coumarins or quinolinones and sulfanylating reagents ,. The representative approach for 3‐sulfanylcoumarins or 3‐sulfanylquinolinones includes the reaction of hydroxycoumarins and hydroxyquinolinones with the corresponding thiols and disulfides .…”
Section: Methodsmentioning
confidence: 99%
“…Various research groups have reported the I 2 -catalyzed crossdehydrogenative coupling of arene-/heteroarene-/alkanethiols with differentn ucleophiles in the presence of DMSO,aperoxide, or O 2 as the oxidant( Ta ble1). [83][84][85][86][87][88][89][90][91][92][93][94] The nucleophile attacks 403,w hich is generated by iodination of disulfide 402 resulting from the oxidative dimerization of thiol 401,t op roduce the product 404 with the elimination of HI. Oxidation of HI regenerates I 2 forthe next catalytic cycle.…”
Section: Heteroatom Activation To Form Ah Etàibond As Ak Ey Intermediatementioning
confidence: 99%